Embedding Maqasid Shariah in Modern Business Strategy: A Pathway to Ethical Sustainability - Adam Hafidz Al Fajar; Ryan Reynolds (PT. Islamic Research Publisher, 2024)
This research aims to explore the application of Maqasid Shariah principles in modern business, which includes the protection of religion, life, intellect, progeny, and wealth, as an ethical framework to align economic goals with social responsibility. This research uses a qualitative method with a literature study approach, analysing related literature to gain in-depth insights. The research steps include data reduction, data presentation, and conclusion drawing. Data reduction was conducted by selecting relevant literature based on quality and relevance, while data presentation was carried out through matrices and diagrams to identify the relationship between Maqasid Shariah principles and modern business elements, such as ethical decision-making and sustainability. The results show that the implementation of Maqasid Shariah principles can increase consumer trust, promote business sustainability, and attract investors through an ethical approach. Businesses that integrate these values tend to be more inclusive and socially responsible. However, the research also found significant challenges, including limited understanding of Maqasid Shariah, commercial pressures, and regulatory barriers. Proposed solutions include education, cross-sector collaboration, and policy harmonisation. Academically, this study contributes to the growing discourse on Islamic business ethics by developing a conceptual linkage between Maqasid Shariah and contemporary sustainability paradigms, particularly Environmental, Social, and Governance (ESG) principles and stakeholder-oriented business models. It also extends the application of Maqasid Shariah beyond its traditional legal and theological domains into the field of modern business management, providing a comprehensive framework for integrating ethical, social, and economic objectives. With these findings, this research contributes to the advancement of both theory and practice in modern business by offering an ethically grounded and sustainability-oriented business framework.